2011
DOI: 10.5483/bmbrep.2011.44.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic alcohol consumption on expression levels of APP and Aβ-producing enzymes

Abstract: Chronic alcohol consumption contributes to numerous diseases, including cancers, cardiovascular diseases, and liver cirrhosis. Epidemiological studies have shown that excessive alcohol consumption is a risk factor for dementia. Along this line, Alzheimer's disease (AD) is the most common form of dementia and is caused by the accumulation of amyloid-β (Aβ plaques in neurons. In this study, we hypothesized that chronic ethanol consumption is associated with pathological processing of APP in AD. To investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…As AD is a risk factor for dementia, prolonged alcohol consumption has been shown to have a toxic effect on amyloid precursor protein. This leads to an accumulation of beta-amyloid in neurons from alcohol dependent rats, perhaps mediated through increased production of reactive oxygen species and mitochondrial dysfunction [ 70 ]. Results from human studies, however, have been more equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…As AD is a risk factor for dementia, prolonged alcohol consumption has been shown to have a toxic effect on amyloid precursor protein. This leads to an accumulation of beta-amyloid in neurons from alcohol dependent rats, perhaps mediated through increased production of reactive oxygen species and mitochondrial dysfunction [ 70 ]. Results from human studies, however, have been more equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…To date there is no evidence that EtOH could be involved in the development of AD. Although some studies reported that EtOH may alter amyloid precursor protein (APP) and APP-processing enzymes (Kim et al, 2011), may cause neuritic plaques in rats (Paula-Barbosa and Tavares, 1984), may increase levels of hyperphosphorylated tau (Sun et al, 2005), and may favor Aβ production (Lahiri et al, 2002), a direct correlation between AD and EtOH consumption has not been found (Graves et al, 1990; Rosen et al, 1993; Tanaka et al, 2002; Aho et al, 2009). Several studies suggest a protective effect of moderate chronic EtOH on AD development (Anstey et al, 2009; Tyas, 1996).…”
mentioning
confidence: 99%
“…Ethanol exposure of mice for 4 weeks increased APP levels and BACE1 expression, promoted Aβ production, increased plaque deposition, and worsened cognitive deficits [ 33 ]. Adult rats fed alcohol for 5 weeks had increased levels of APP and BACE1 in several brain regions and increased presenilin-1 and nicastrin in the hippocampus [ 34 ]. Long-term alcohol consumption significantly impaired spatial memory in adult rats, which may be a contributing factor to development of AD [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer’s disease (AD), microglial phagocytosis of oligomeric and aggregated forms of amyloid beta (Aβ) is one of the key means by which amyloid burden is limited [ 26 , 27 ]. Several studies suggest that alcohol may be a risk factor for AD [ 28 31 ], and there are also reports that alcohol increases amyloid processing and deposition [ 32 34 ]. However, whether alcohol influences the ability or efficacy of microglial cells to internalize Aβ has not been examined, although several studies have shown that peripheral macrophages have reduced phagocytotic activity after alcohol treatment [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%